READING LITERACY MENTORING FOR MIS TARBIYATUL ISLAMIYAH SUKODONO STUDENTS THROUGH VISUAL-BASED TEXT READING ACTIVITIES - Nailul Al Chumairoh Machfud; Asyhari Zubair; Agus Setyawanto; Dwi Astutiek (Jurnal Pengabdian Masyarakat Sabangka, 2026)
This community service program aims to improve the reading literacy skills of MIS Tarbiyatul Islamiyah students through visual-based text reading activities. The method applied was literacy mentoring using a participatory approach, involving students in guided reading, reading aloud in front of the class, and simple discussions supported by visual media. The program was conducted through several stages, including initial observation, implementation of reading assistance, and reflection. The results indicate that students became more active and enthusiastic in reading activities, showed increased confidence in reading aloud, and were able to better understand the reading texts. The use of visual media helped create a more engaging learning environment and supported students’ reading comprehension. This program demonstrates that visual-based reading literacy mentoring is an effective approach to enhancing reading literacy among MIS Tarbiyatul Islamiyah students.